The prevalence of coeliac disease in Libyan children with type 1 diabetes mellitus - Ashabani, Abdelhakim; Abushofa, Umaima; Abusrewill, Suliman; Abdelazez, Mahmoud; Tucková, Ludmila; Tlaskalová-Hogenová, Helena (Diabetes/metabolism research and reviews, 2003)
BACKGROUND: Diagnosis of atypical and silent forms of coeliac disease (CD) is important because of its serious complications. Increased prevalence of coeliac disease worldwide in individuals with type 1 diabetes mellitus (DM) was described. There are no data on the prevalence of CD in the Libyan population and Libyan DM patients. The aim of this study was to test the occurrence of CD-related markers in a group of Libyan children with DM. METHODS: A cohort of 234 Libyan children with DM (121 males and 113 females) aged between 2 and 25 years and 50 healthy school children were screened for CD using the enzyme-linked immunosorbent assay (ELISA) for IgA and IgG antigliadin (AGA), anti-tissue transglutaminase (tTG), and anticalreticulin antibodies. An IgA antiendomysial antibody (EmA) was determined by immunofluorescence. RESULTS: Fifty patients (21.3%) were positive for IgA- and/or IgG-AGA, tTG, and anticalreticulin antibodies. Nineteen of these patients were EmA positive and seven were EmA negative. From the EmA negative patients we found that five sera with IgA deficiency had high IgG class in antigliadin, anti-tissue transglutaminase, and anticalreticulin antibodies. All these patients underwent intestinal biopsy. Twenty-four had clear histological (atrophy) evidence of CD including the EmA negative patients with IgA deficiency; prevalence of CD in this study was thus 10.3%. CONCLUSION: The prevalence of CD in diabetic children in Libya was found to be higher than in several European countries. Serological markers are useful for identifying DM patients who should undergo a small intestinal biopsy.
Keywords: Calreticulin; Libya; Biopsy; Transglutaminases; Humans; imunoglobulin G; dítě; prevalence; kohortové studie; Child; Libye; střevní sliznice; Female; dospělí; lidé; Immunoglobulin A; transglutaminasy; biopsie; Cohort Studies; předškolní dítě; diabetes mellitus 1. typu; Adult; gliadin; celiakie; ženské pohlaví; Male; Adolescent; Gliadin; kalretikulin; Celiac Disease; imunoglobulin A; Prevalence; mužské pohlaví; Immunoglobulin G; Child, Preschool; Intestinal Mucosa; Diabetes Mellitus, Type 1; mladiství